Synthesis of indoles via intermolecular and intramolecular cyclization by using palladium-based catalysts - Ayesha; Bilal, Muhammad; Rasool, Nasir; Khan, Samreen Gul; Rashid, Umer; Altaf, Humaira; Ali, Imtiaz (MDPI AG, 2021)
As part of natural products or biologically active compounds, the synthesis of nitrogen-containing heterocycles is becoming incredibly valuable. Palladium is a transition metal that is widely utilized as a catalyst to facilitate carbon-carbon and carbon-heteroatom coupling; it is used in the synthesis of various heterocycles. This review includes the twelve years of successful indole synthesis using various palladium catalysts to establish carbon-carbon or carbon-nitrogen coupling, as well as the conditions that have been optimized.